Fundamental concepts and skills for nursing - DeWit, Susan C. (Philadelphia : Elsevier, 2001)
"The first edition of Fundamental Concepts and Skills for Nursing rapidly became the textbook of choice for both students and instructors. By providing just the right level of coverage of the fundamental concepts and skills for the LPN/LVN student, combined with a superior teaching and learning package, this new edition will continue to be the textbook of choice for many years to come!."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Nursing; Nursing Process; Nursing Care; Soins infirmiers